2023
DOI: 10.7573/dic.2023-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin and management of liver function in nonalcoholic steatohepatitis: a case report

Abstract: Non-alcoholic fatty liver disease (NAFLD) and its progressive form (non-alcoholic steatohepatitis; NASH) are the main reason for chronic liver disease in the general population, characterized by fat accumulation in hepatocytes (steatosis) and anomalies in liver biochemical analyses. To date, no pharmacological agents have been approved for NAFLD or NASH treatment. However, silymarin, the active ingredient in milk thistle, has been used in the last decades for the treatment of several liver diseases. In this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…This meta-analysis also showed that silymarin is well tolerated and could therefore be of great interest in the treatment of NAFLD, especially NASH. Several recent clinical trials have also supported these findings [ 124 , 125 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 61%
See 1 more Smart Citation
“…This meta-analysis also showed that silymarin is well tolerated and could therefore be of great interest in the treatment of NAFLD, especially NASH. Several recent clinical trials have also supported these findings [ 124 , 125 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 61%
“…The plant methanolic extract contains a significant content of bioactive phytochemicals such as terpenoids, betanins, carotenoids, polyphenols, saponins, and phytoecdysteroids [ 126 ]. Several studies have recently described quinoa as a highly promising functional food component to treat obesity and metabolic diseases such as metabolic syndrome, T2DM and NAFLD [ 125 127 ]. A study investigating the effects of quinoa intake on high-fed rats suggests that quinoa phytochemicals are the causes of lipid metabolism dysfunction regulation, leading to a resolution of IR, liver steatosis decrease, and anti-inflammation and antioxidative quinoa properties [ 128 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 99%
“…Various studies have been conducted or are ongoing to further confirm the evidence on silymarin and improve its clinical use. [54][55][56][57][58][59]…”
Section: Role Of Oxidative Stress Management In Mafld Treatmentmentioning
confidence: 99%
“…In the case reports published by Chantarojanasiri 6 and Torre, 5 liver stiffness and controlled attenuation parameter assessments by transient elastography (Fibroscan system) were used to evaluate and monitor hepatic steatosis over time, whilst a hepatic fibrosis biomarker (FIB-4 index) was used to assess the degree of liver fibrosis in the case presented by Hashem. 7 …”
Section: Reviewmentioning
confidence: 99%
“…This review is an opening paper to the clinical case collection entitled 'Current clinical use of silymarin in the treatment of toxic liver diseases: a case series', focused on the management and treatment of major liver diseases with silymarin. [5][6][7][8][9][10]…”
Section: Introductionmentioning
confidence: 99%